Comparison Of Intravenous Iron Sucrose Versus Oral Iron For The Treatment Of Iron Deficiency Anaemia In Pregnancy (The Review of Diabetic Studies, 2025)
Background: Iron deficiency anemia (IDA) is common in pregnancy, especially in developing countries. Oral iron is the standard treatment, but gastrointestinal side effects limit its effectiveness. Intravenous iron sucrose provides an alternative with fewer side effects and better efficacy.Objective: To compare the efficacy and safety of intravenous iron sucrose versus oral ferrous sulfate for treating IDA in pregnancy.Methods: A prospective, randomized, open-label study was conducted at a tertiary care hospital. 100 pregnant women with IDA between 14-35 weeks gestation were randomized to receive either intravenous iron sucrose or oral ferrous sulfate. Hemoglobin, packed cell volume, mean corpuscular volume, and reticulocyte count were assessed at baseline, 2 weeks, 4 weeks, and at term.Results: Intravenous iron sucrose resulted in a significantly greater increase in hemoglobin and packed cell volume at 2 weeks, 4 weeks, and at term. There were fewer gastrointestinal side effects in the intravenous group (0% vs 44% for oral iron). Both groups had similar iron requirements.Conclusion: Intravenous iron sucrose is more effective and better tolerated than oral ferrous sulfate for treating moderate-to-severe IDA during pregnancy. It offers faster anemia correction, fewer side effects, and improved maternal outcomes.